Caterpillar Cultivation Technology Transfer At Hongkong Caterpillar Farmer Group At Oro-oro Ombo, Batu City - Rini Yulianingsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
ABSTRACT Hongkong caterpillar cultivation is one of the actvities of people in Oro-oro Ombo Village, Batu. Its production capacity is 2-3 tons per week or 8-12 tons per month. The products are in the form of hongkong caterpillars and feces. Marketing area of Hongkong cartepillar is some cities at Java. The problems faced by farmer group are low production efficiency and capacity because some steps in cultivation are done manually. Alternative solution is technology transfer by mechanical equipment in cultivation including cutting machine, sieving, and semi automatic shredder. The results of the implementation are an increase in production efficiency, product quality and production capacity of Hongkong cater-pillars. Improvement of existing pro-duction systems with the application of Good Manufacturing Practice, logbook production and management of SME financial statements that is more pro-fessional, besides increasing awareness of health and safety among workers that suggests to increase production capacity that is expected to increase revenue.Keyworda: efficiency of production, Hongkong caterpillars, production capacity